Testimonies and Secrets : The Story of a Nova Scotia Family, 1844-1977 - Mennel, Robert M. (Book collections on Project MUSE., 2013)
A story of vivid personalities and episodes, by turns sad, conflicted, joyful, bitter, funny and reflective, Testimonies and Secrets will be read with pleasure by scholars and general readers alike.